Development of Gender-Based Interactive Learning Media Assisted by Augmented Reality - Wigati, Indah; Rohayati, Enok; Yuniar, Yuniar (Buana Gender: Jurnal Studi Gender dan Anak, 2024)
Demands for the use of technology globally continue to grow rapidly in the world of education. Implementation of technology in education can take the form of using digital-based learning media. The aim of this research is to produce a product in the form of an interactive module assisted by gender-based augmented reality on human nature material. This type of research is development or Research of Development (R&D) with a 4-D design which includes define, design, develop and disseminate. Respondents in this research were media experts, material experts, language experts, gender experts, educators and students. Product trials were carried out on lecturers and students involved in Islamic Education lectures. The product validity value obtained an average of 94.25% with a very valid category. Based on the validation results, it can be stated that the gender-based augmented reality-assisted interactive module on human nature material is a valid product and can be used as teaching material in learning Islamic Education.